2009
DOI: 10.1177/1476718x08098353
|View full text |Cite
|
Sign up to set email alerts
|

grandparents as educators and carers in China

Abstract: Many grandparents play a significant role as educators and carers of children in the preschool years. Recently, this role has become the focus of much early childhood research as challenges facing grandparent carers and grandparent-headed households increasingly become an economic and social issue. Using survey data from China we explore the role of grandparents who have a primary care responsibility for a young child and discuss this contribution to the family in relation to quality of care and education. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 12 publications
0
25
0
Order By: Relevance
“…In China, children usually stay at home until three years of age, and are often taken care of by grandparents living in the same household as the children, or in close proximity. Although nuclear family is the main construct in current China, extended family households (with three or more generations) still constitute a large proportion 30 , and it is a traditional, common and acceptable idea that grandparents involve in childcare, especially in early childhood 31 . Due to the one-child policy enacted in late 1970s, most families in urban China have one child only.…”
Section: Discussionmentioning
confidence: 99%
“…In China, children usually stay at home until three years of age, and are often taken care of by grandparents living in the same household as the children, or in close proximity. Although nuclear family is the main construct in current China, extended family households (with three or more generations) still constitute a large proportion 30 , and it is a traditional, common and acceptable idea that grandparents involve in childcare, especially in early childhood 31 . Due to the one-child policy enacted in late 1970s, most families in urban China have one child only.…”
Section: Discussionmentioning
confidence: 99%
“…18 Nyland et al's work add to the above the importance of factoring in cultural change and teasing out how this reconfigures age as a relation of power. 19 In their research in the Chinese context they found that grandparents not only care for grandchildren out of plain necessity, but also 'because care of young children has traditionally been a right and expectation of grandparents'. 20 However, these rights and expectations have become contested and subject to change under the pressure of wider social transformations.…”
Section: Care Work Inter-generational Relations and Gender In Contexmentioning
confidence: 98%
“…In the case of migrant grandparents, it has been argued that grandparental caregiving could be regarded as a means of social engagement and social activity (Waldrop and Weber, 2001;Nyland et al, 2009;Arpino and Bordone, 2014;Burn and Szoeke, 2015;Bulanda and Jendrek, 2016), which could fulfill the need for social connectedness. As argued by disengagement theory, people gradually disengage from social life as they grow older (Cumming et al, 1960), making them more likely to lose social ties that were previously available to them.…”
Section: Grandparental Caregiving Boosts Social Connectednessmentioning
confidence: 99%